How early clinical experiences in rural communities influence student learning about rural generalism considered through the lens of educational theory (Canadian Medical Education Journal, 2024)
Introduction: Rural communities have poorer health compared to urban populations due partly to having lesser healthcare access. Rural placements during medical education can equip students with the knowledge and skills to work in rural communities, and, it is hoped, increase the supply of rural physicians. It is unclear how students gain knowledge of rural generalism during placements, and how this can be understood in terms of place-based and/or sociocultural educational theories. To gain insight into these questions we considered the experiences of pre-clerkship medical students who completed two mandatory four-week rural placements during their second year of medical school.Methods: Data was collected using semi-structured interviews or focus groups, followed by thematic analysis of the interview transcripts.Results: Rural placements allowed students to learn about rural generalism such as breadth of practice, and boundary issues. This occurred mainly by students interacting with rural physician faculty, with the effectiveness of precepting being key to students acquiring knowledge and skills and reporting a positive regard for the placement experience.Discussion: Our data show the central role of generalist physician preceptors in how and what students learn while participating in rural placements. Sociocultural learning theory best explains student learning, while place-based education theory helps inform the curriculum. Effective training and preparation of preceptors is likely key to positive student placement experiences.